The Effect of The Science, Technology, Engineering, and Mathematics (STEM) Learning Model on Students' Numeracy Literacy Skills - Wahyu Rizaldy Siregar; Siti Maysarah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to determine the effect of the STEM learning model on students' numeracy literacy skills. The STEM (Science, Technology, Engineering, and Mathematics) learning model is an interdisciplinary instructional approach that integrates concepts and practices from science, technology, engineering, and mathematics to solve real-world problems. This model emphasizes inquiry-based learning, critical thinking, and problem-solving skills, encouraging students to apply knowledge across disciplines in a cohesive and meaningful way. STEM education aims to enhance students’ cognitive engagement and prepare them for future academic and career challenges in a rapidly advancing technological world. The study was conducted at SMP Darussalam with a sample size of 27 students. A quantitative approach was employed, utilizing data analysis techniques such as normality and homogeneity tests. Subsequently, a t-test was conducted to assess the influence of the STEM model in mathematics learning. The results of the study indicate a significant effect on students' numeracy literacy skills, as evidenced by the average test scores, which increased from 18,852 on the pretest to 30,704 on the posttest. This finding suggests that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted.